2015
DOI: 10.1515/intox-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant modulation of nevirapine induced hepatotoxicity in rats

Abstract: HIV/AIDS related mortality has been dramatically reduced by the advent of antiretroviral therapy (ART). However, ART presents with associated adverse effects. One of such adverse effects is hepatotoxicity observed with nevirapine (NVP) containing ART. Since previous studies showed that NVP hepatotoxicity may be due to oxidative stress via generation of oxidative radicals, this study sought to evaluate the protective effects of antioxidants in alleviating NVP induced hepatotoxicity. Rats were divided into 6 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Highly active antiretroviral therapy (HAART) has hitherto reduced the burden of HIV-related illnesses and deaths among HIV patients compared to HIV positive but untreated [1]. Nevertheless, HAART induces oxidative stress [2,3,4] and life expectancy in HAART treated HIV patients is shorter than the uninfected population [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly active antiretroviral therapy (HAART) has hitherto reduced the burden of HIV-related illnesses and deaths among HIV patients compared to HIV positive but untreated [1]. Nevertheless, HAART induces oxidative stress [2,3,4] and life expectancy in HAART treated HIV patients is shorter than the uninfected population [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both in vivo and in vitro studies have reported antiretroviral drugs-induced ROS generation [1][2][3]. The polymerase gamma toxicity theory of the nucleoside reverse transcriptase inhibitors (NRTIs (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in mice with MSG-induced neurotoxicity, an increase in Plasma and brain SOD and NO was observed; with nevirapine mitigating MSG-induced oxidative stress and antioxidant derangement when administered at 7, 15 and 30 mg/kg. A number of other studies have also reported increased lipid peroxidation and decreased antioxidant activity (superoxide dismutase and catalase) in the plasma or tissues of rats administered nevirapine alone with increasing doses (36,37).…”
Section: Discussionmentioning
confidence: 91%
“…Similarly Awodele and co-researchers reported the ameliorative effects of vitamins C and E on nevirapine-induced hepatotoxicity in rats. 59 Also, Naglaa et al, 2015 60 reported the beneficial effect of NAC on acetaminophen-induced hepatotoxicity in rats.…”
Section: Discussionmentioning
confidence: 99%